New global priority for mental health – reasons for optimism and concern - Nigel Crisp (BJPsych International, 2016)
Mental health is a core part of the Sustainable Development Goals (SDGs) agreed by the United Nations General Assembly. This follows on from the World Health Organization's 2013 Global Action Programme. The World Bank is also expected to give mental health greater priority. Moreover, mental health is now seen as essential in disaster relief management. However, although global policy towards mental health has improved, there are only rare examples where this has been translated at scale into action. There are, nonetheless, reasons for optimism in the new policy background, in the many innovative practical developments around the world and in the way that evidence is being gathered and learning shared. The understanding that mental health is intimately connected to physical, social, environmental and economic health – which is so evident in the SDGs – represents a major change in mind-sets globally.